Rancang Bangun Sistem Informasi Pariwisata Kecamatan Muaragembong Berbasis Web - Dewi Yuliandari; Oryza Gilang; Feri Prasetyo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2017)
In this era of globalization along with the development and progression of increasingly sophisticated technology, the flow of information must be delivered quickly and accurately. Widespread activity and human need for information makes it requires a computer with Internet access to be able to resolve the issues and activities quickly and accurately.Technological developments in the field of communication today helped humans in various areas of life, including in the world of tourism. One of the technological advances in the field of communication that can be utilized for the provision of information and promotion of tourism is the internet. Indonesia has pontesi state of tourism in different regions of one of them in the area of western Java brass. Based on the above understanding, the tourism point of view as an alternative to increase local revenue. In order to promote tourism in the region of western Java brass we made a tourism website in order to facilitate the community in accessing any information relating to tourism in the region of western Java brass.Muaragembong Regency is one of the tourist centers potensional in West Java province, where a great variety of cultural and interesting attractions as well as typical food full of flavor.Come and enjoy the beauty and the natural beauty of the exotic nature, rich culture and diverse challenges. Intisari—Perkembangan teknologi di bidang komunikasi saat ini banyak membantu manusia di berbagai bidang kehidupan,termasuk didalam dunia pariwisata. Salah satu kemajuan teknologi di bidang komunikasi yang dapat di manfaatkan untuk penyediaan informasi dan promosi kepariwisataan adalah internet. Negara indonesia memiliki pontesi kepariwisataan di berbagai daerah salah satunya di daerah Muaragembong jawa barat. Berdasarkan pemahaman di atas maka pariwisata di pandang sebagai salah satu alternatif untuk meningkatkan pendapatan daerah. Demi mempromosikan pariwisata di daerah Muaragembong jawa barat kami membuat sebuah website kepariwisataan agar mempermudah masyarakat dalam mengakes segala informasi yang berkaitan dengan pariwisata di daerah Muaragembong jawa barat.Kecamatan Muaragembong merupakan salah satu sentra wisata potensional di Provinsi Jawa Barat, dimana banyak ragam budaya dan obyek wisata yang menarik serta makanan khas yang penuh akan cita rasa. Datang dan nikmatilah keindahan serta keasrian alam yang alami nan eksotis, kaya akan tantangan dan culture yang beragam.